A waterfowl seed-dispersal network from the Neotropical region is nested and modular - Silva, Giliandro G. (2023)
Seed dispersal by vertebrates is fundamental for the persistence of plant species, forming networks of interactions that are often nested and modular. Networks involving angiosperms and frugivorous birds are relatively well-studied in the Neotropical region, but there are no previous studies of networks involving waterbirds. Here, we describe the structure of a Neotropical waterfowl seed-dispersal network and identify the species that have an important role for the network structure. We used information on 40 plant taxa found in fecal samples of five common waterfowl species to calculate the nestedness (NODF), weighted nestedness (WNODF), modularity, and weighted modularity of the network. We found that the network was nested, with yellow-billed teal showing the highest contribution both to nestedness and weighted nestedness. Twenty-four plant species contributed positively to weighted nestedness, with Salzmann's mille graines presenting the highest influence both to nestedness and weighted nestedness. The network was modular, but the weighted modularity was not significant. These results need to be considered with caution due to incomplete interaction sampling for two species. Ringed teal, Brazilian teal, and yellow-billed teal were considered hub modular species. Among plants, beak sedges and water snowflake were considered modular hub species, while Salzmann's mille graines and spikerush were network connectors. The structure of this Neotropical waterbird seed-dispersal network differed from the only previous waterfowl network study, from Europe, which found similar level of nestedness but no significant modularity. We include several possible explanations for this discrepancy and identified priorities for future research into waterbird–plant interaction networks. Abstract in Portuguese is available with online material.